2016
DOI: 10.1111/agec.12227
|View full text |Cite
|
Sign up to set email alerts
|

Yield and income effects of rice varieties with tolerance of multiple abiotic stresses: the case of green super rice (GSR) and flooding in the Philippines

Abstract: With the increasing frequency of extreme climatic events, the new challenge is to develop rice varieties that are tolerant of drought, water submergence, and salinity. There are now new high-yielding green super rice (GSR) cultivars developed at the International Rice Research Institute with increased tolerance to multiple abiotic stresses. But a clear understanding of the economic benefits of these varieties under farmers' production environments is not yet fully understood. In this article, we assess the yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 23 publications
0
22
0
2
Order By: Relevance
“…of drought (Zhang 2007). In addition, because of the frequent occurrences of extreme weather worldwide, the conflicts between agricultural production and environmental resources are becoming increasingly intense (Yorobe et al 2016). Therefore, ensuring the food security and sustainable development of agriculture has become a key strategic concern worldwide.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…of drought (Zhang 2007). In addition, because of the frequent occurrences of extreme weather worldwide, the conflicts between agricultural production and environmental resources are becoming increasingly intense (Yorobe et al 2016). Therefore, ensuring the food security and sustainable development of agriculture has become a key strategic concern worldwide.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…An excellent socioeconomic performance has been achieved by the popularization of GSR varieties in the target African and Asian countries. Socioeconomic assessment of some GSR varieties bred for rainfed and irrigated lowland environments in the Philippines and Bangladesh showed that GSR varieties contribute significantly to the yield and net income of farmers (Ali et al 2012;Yorobe et al 2016). Compared with conventional rice, GSR varieties showed significantly enhanced yield and economic output (by 0.89-1.83 tons and USD 230.90 per hectare, respectively) and disease/insect resistance (Yorobe et al 2016).…”
Section: International Popularization and Application Of Gsr Varietiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They find that the use of this risk-reducing variety leads to higher adoption of other improved agricultural inputs and practices, such as adoption of a more labor-intensive planting, inorganic fertilizer application, and credit utilization. One issue of abiotic stress-tolerant varieties is that the benefits of adoption become visible only when the specific stress, which they are tolerant to, appears (Yamano, Luz, Habib, & Kumar, 2018;Yorobe et al, 2016). The study of submergence-tolerant rice variety adoption in Bangladesh shows that experience of submergence in the previous year increases adoption (Yamano et al, 2018).…”
Section: Adoption Of Improved Varietiesmentioning
confidence: 99%
“…In the case of stress‐tolerant crops, their benefits become visible only under the specific stresses they are tolerant to and shows an advantage in terms of yield when there is climatic event like flood (Yorobe et al., ). Thus, learning opportunities of stress‐tolerant crops are limited for farmers.…”
Section: Technology Development and Adoptionmentioning
confidence: 99%